Carbon monoxide: a critical quantitative analysis and review of the extent and limitations of its second messenger function - Levitt DG; Levitt MD (Dove Medical Press, 2015)
David G Levitt,1 Michael D Levitt2 1Department of Integrative Biology and Physiology, University of Minnesota, Minneapolis, MN, USA; 2Research Service, Veterans Affairs Medical Center, Minneapolis, MN, USA Abstract: Endogenously produced carbon monoxide (CO) is commonly believed to be a ubiquitous second messenger involved in a wide range of physiological and pathological responses. The major evidence supporting this concept is that CO is produced endogenously via heme oxygenase-catalyzed breakdown of heme and that experimental exposure to CO alters tissue function. However, it remains to be conclusively demonstrated that there are specific receptors for CO and that endogenous CO production is sufficient to alter tissue function. Unlike other signaling molecules, CO is not significantly metabolized, and it is removed from cells solely via rapid diffusion into blood, which serves as a near infinite sink. This non-metabolizable nature of CO renders the physiology of this gas uniquely susceptible to quantitative modeling. This review analyzes each of the steps involved in CO signaling: 1) the background CO partial pressure (PCO) and the blood and tissue CO binding; 2) the affinity of the putative CO receptors; 3) the rate of endogenous tissue CO production; and 4) the tissue PCO that results from the balance between this endogenous CO production and diffusion to the blood sink. Because existing data demonstrate that virtually all endogenous CO production results from the routine “housekeeping” turnover of heme, only a small fraction can play a signaling role. The novel aspect of the present report is to demonstrate via physiological modeling that this small fraction of CO production is seemingly insufficient to raise intracellular PCO to the levels required for the conventional, specific messenger receptor activation. It is concluded that the many physiological alterations observed with exogenous CO administration are probably produced by the non-specific CO inhibition of cytochrome C oxidase activity, with release of reactive oxygen species (ROS) and that this ROS signaling pathway is a potential effector mechanism for endogenously produced CO. Keywords: cytochrome, oxygenase, Krogh cylinder model, ROS, heme